The Effect of Tax Justice, Tax Audits and Tax Rates on Taxpayer Perceptions of Tax Evasion - Maulana, Amanda Atturaini; Dyarini, Dyarini (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The purpose of this study is to examine how taxpayers' perceptions of tax evasion are impacted by tax justice, tax audits, and tax rates. With a sample size of 100, the population in this study is made up of individual taxpayers who are registered with KPP Pratama Jakarta Kebayoran Lama. Probability sampling combined with a basic random sample approach is the methodology employed in this investigation. Descriptive statistical approaches are employed in quantitative research. IBM SPSS version 25 is used to examine the data that was gathered. According to the study's findings, taxpayers' opinions of tax evasion are significantly improved by tax justice. On the other hand, taxpayers' opinions of tax evasion are significantly impacted negatively by tax audits and tax rates. In general, taxpayers' perceptions of tax evasion increase with the degree of tax fairness. In the meanwhile, proportionate tax rates and more stringent tax audits might lessen taxpayers' propensity to consider tax evasion as a possibility.